A partner in progress?: Shell-BP's role in Nigeria during the transition to independence, 1946-67 - Minton, Christopher Philip Thomas (2019)
This thesis offers a critical overview of Shell-BP’s operations at the policy level between 1946 and 1967. It analyses the strategies devised and implemented by Shell-BP to deal with decolonisation and the complex business environment created as a result. It also investigates what sort of relationship existed between the company and nationalists, and between the company and the British government, both before and after Nigerian independence on 1 October 1960. Each of the four chapters addresses one key aspect of Shell BP’s strategy for independence, the objective of which was to entrench its position by attaining new legitimacy. Chapter one analyses the company’s development role as Nigeria’s partner in progress. Chapter two explores Shell BP’s public relations policy to emphasise its development role while encouraging cautious optimism. Chapter three assesses the firm’s efforts to establish a local, naturalised identity and to replace expatriates with Nigerians, even on its board of directors, without transferring overall control away from the metropole. Finally, chapter four examines Shell-BP’s industrial relations strategy to present itself as both a reliable partner for government and a model employer. Shell-BP and the Nigerian oil industry have been overlooked in the literature on oil and imperial business and, as a result, the firm’s role in the transition to independence has not been explored fully. The present study constitutes a substantial contribution to these areas and, contrary to conventional wisdom, demonstrates the significance of Shell BP and the oil industry in Nigeria’s modern history prior to the massive revenues accrued in the 1970s. The thesis finds that while Shell-BP was able to secure co-operative partnerships with nationalists in government, its relations with other nationalists were defined by conflict, and contends that, while there is little evidence that Shell-BP influenced official policy on decolonisation, the British government offered ongoing assistance and protection to the company. It concludes that Shell BP’s overall strategy for independence was a success, even if the results for Nigeria were not always particularly edifying.